ANALISIS PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE (GCG) DI BANK BRI SYARIAH PUSAT - Isfandayani, Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
This research is to know how to apply the principles of Good CorporateGovernance (GCG) at Bank BRISyariah Pusat, what are the obstacles faced inapplying GCG principles and how to overcome the obstacles that happened inapplying GCG principles at Bank BRI Syariah. The method used is the method ofqualitative naturalistic research with data collection techniques that is observation,interview and documentation. The results conclude that BRISyariah has applied GCGprinciples in accordance with applicable laws and regulations. There are five GCGprinciples applied by BRISyariah in accordance with Bank Indonesia Regulation(PBI) no. 11/33 / PBI / 2009 is transparency, accountability, responsibility,professional, fairness. Implementation of the principles of Good CorporateGovernance (GCG) under the authority of Bank BRISyariah can be said to be good,effective and in accordance with the provisions of applicable legislation.